The 16 Undeniable Laws of Communication apply them and make the most of your message - Maxwell, John C. (Maxwell Leadership, 2023)
It?s been said that public speaking is the number one fear of most people, with death being second. ?This means,? said comedian Jerry Seinfeld, ?if you have to be at a funeral, you would rather be in the casket than doing the eulogy.?
Includes index
Keywords: Leadership